BETWEEN THE MAGIC OF THE FAIRYTALE AND THE ARRAY OF CONNOTATIONS – WHO DID ALICE MEET IN WONDERLAND - Seweryn, Agnieszka Maria (Porównania, 2018)
This paper focuses on the issues of translating personal proper names in Polish versions of Lewis Carroll’s novel “Alice’s Adventures in Wonderland”. The main intention of this work is to present cultural connotations of names invented by the author and describe their specificity and significance. It is also an attempt to analyze translation strategies applied in the texts to explain possible reasons for the translators’ decisions. The basic corpus consists of an original version of the novel with the footnotes made by Martin Gardner and four new Polish versions of “Alice...”, issued after 1990.